Incorporating a redox active entity to attain electrical bistability in a polymer semiconductor. Issue 14 (7th April 2021) - Barman, Biswajit K.; Ghosh, Nani Gopal; Giri, Indrajit; Kumar, Chandan; Zade, Sanjio S.; Vijayaraghavan, Ratheesh K.
Abstract : Incorporating a redox active anthraquinone acceptor group to a polymer semiconductor is found to induce electrical bistability. Resistive memory devices based on the redox switch mechanism is thus materialized in a sandwich device. Abstract : Owing to the advantages of 3-D printable stack, scalability and low cost solution state production, polymer-based resistive memory devices have been identified as the promising alternative for conventional oxide technology. Resistive memory devices based on the redox switch mechanism is particularly found to yield high precision with respect to the operational voltages. Reversible non-volatile resistive state switching was realized with high device yield (>80%), with a redox-active chemical entity conjugated to the polymeric semiconductor, and the control experiments with the model compound confirmed the imperative role of the redox-active anthraquinone center in the polymeric backbone. Highly uniform nanodomains and the trap free layers excluded the possibilities of other known switching mechanisms. Optical studies and the molecular modelling data assert the presence of strong charge transfer characteristics upon optical excitation due to the insertion of the anthraquinone unit, which was detrimental in exhibiting bistable conductive states in electrical bias as well.